An Overview of Procedurally Generating Virtual Environments - Liu, Yinghu (International Journal of Computer Science and Information Technology, 2024)
Procedural Generation is a method of using computers to generate content, allowing users to manually create content for virtual worlds is a very time consuming and laborious task, with the development of computer hardware, Procedural Generation is a good alternative, Procedural Generation content can be used as models or sketches to provide inspiration for the artist or to improve efficiency, this paper focuses on the representative algorithms used in Procedural Generation, which are commonly used to produce architecture, plants and terrain.